Africa and the challenge of globalization - Herbst, Jeffrey (2009)
This paper provides an overview of Africa's economic performance. Although the continent appeared headed for economic success in the early days of independence, based particularly on natural resource endowments, Africa's economic growth has stagnated while the rest of the world has experienced continuous, often spectacular, growth. The countries in Africa that have had the worst performance are those that contain the majority of the population. These states, in particular, suffer most from a crisis of governance and lack the policy and legal frameworks to grow quickly. The states in Africa can be divided into six categories and each grouping faces a different set of challenges from globalization: 1) high performers ready to globalize; 2)coutries on an upward trajectory; 3)large, poorly performing countries; 4)poorly performing countries; 5)countries in collapse; and 6)old producing countries. Only the states in the first two groupings are currently able to participate in the globalized economy.